Cybergonomics: Proposing and justification of a new name for the ergonomics of Industry 4.0 technologies - Pouyakian, Mostafa (Frontiers in Public Health, 2022)
Various subdisciplines of ergonomics science have emerged during the past decades as our insight has been broadened of human and performance. The three main branches of ergonomics have evolved over time focusing on the physical, cognitive, and organizational aspects. But the question is, can these disciplines focus and research enough on the ergonomic aspects of cyberspace and Industry 4.0 technologies? Cyber-technologies of the Fourth Industrial revolution are dramatically imposing themselves on our life and work. This has been led to emerging cyber-aspects for human work and life. Hence, many sciences, mainly applied ones, have upgraded to their cyber versions to deal with the emergent issues, usually with a new name, including the cyber prefix. Cyber-medicine, cyber-health, cyber-commerce, and cyberpsychology are some examples. Also, ergonomics requires a similar look. Ergonomic benefits and threats of Industry 4.0 technologies must be considered in an integrated manner. This paper addresses this issue. First, the emergence and development of ergonomics and its subdisciplines chronologically is reviewed. Then, Cybergonomics as a new name and concept is proposed and defined as the ergonomics of Industry 4.0 era. Justification for this portmanteau is described, and an outline of the new realm is explained. Finally, a research road map is proposed for this new subdiscipline of ergonomics.